Geographical and temporal distribution of cancer survival in teenagers and young adults in England - Geraci, M (Nature Publishing Group, 2009)
BACKGROUND: Between 1979 and 2001, an analysis of cancer survival in young people in England, aged 13 to 24 years, showed overall improvements. However, for some diagnostic groups, little or no increases were observed. The aim of this study was to analyse the regional distribution of cancer survival in teenagers and young adults in England in order to identify patterns and potential for improvements at a regional scale. METHODS: We examined geographical and temporal patterns in relative survival in cancer patients aged 13–24 years in England during the time period 1979–2001. Cancer cases were grouped according to an internationally recognised morphology-based diagnostic scheme. RESULTS: For most diagnostic groups, there was little variation in survival between regions, except for testicular germ cell tumours (P=0.006) and colorectal carcinoma (P=0.002). For certain diagnostic groups, the temporal pattern in survival differed between regions. However, in regions that showed poor survival during the early part of the study period, greatest improvements were observed in groups such as acute lymphoid leukaemia, acute myeloid leukaemia, testicular tumours and melanoma. CONCLUSION: In conclusion, there was a reduction in the differences in survival between regions during the study period.